Pemanfaatan Tumbuhan Sebagai Bahan Pewarna Alami Oleh Suku Dayak Bidayuh Di Desa Kenaman Kecamatan Sekayam Kabupaten Sanggau - Mukarlina, Sri Wahyuni Berlin, Riza Linda (Universitas Tanjungpura, 2017)
Dayak Bidayuh in Kenaman village Sekayam district Sanggau regency consumes much of forest products for their daily needs, one of them is natural dye plants which is used for coloring clothes, yarn, food, crafts, and cosmetics. This research aims to find out the kinds of natural dye plants, the parts used, and the preparation process. This research was conducted February to April 2017. The respondents were chosen through snowball method. Dayak chieftain as the community leader waws taken as the primary respondents. The interview was done in semi-structured technique. The results show that there are 23 species of natural dye plants which include in 20 families, namely Achantaceae, Amaranthaceae, Arecaceae, Asteraceae, Balsaminaceae, Bixaciae, Bonnetiaceae, Combretaceae, Crotonoideae, Cactaceae, Liliaceae, Malvaceae, Meliaceae, Moraceae, Musaceae, Pandanaceae, Rubiaceae, Sterculiaceae, Verbanaceae, Zingiberaceae. Of these 20 families, some of the plants are processed by pounding, boiling, bruising, burning, and then be used.